The Potential Positive Impact of Sup-ported Employment on the Oral Health Status, Attitudes and Behavior of Adults with Intellectual Disabilities - Vasileios Margaritis; Haroula Koletsi-Kounari; Eleni Mamai-Homata; Juliana Kiriakou (Wolters Kluwer Medknow Publications, 2012)
Introduction: Individuals with Intellectual Disabilities (ID) con-stitute a unique but heterogeneous population, which includes a great variety of mental and developmental disorders, as well as congenital syndromes. Nowadays, many persons with mild or moderate ID, with specific training, can make considerable efforts to improve their lives, by having a job in either open or supported employment. On the other hand, since dental caries and periodontal diseases are among the most common secondary conditions affecting people with ID, oral diseases may detract the quality of life from disabled persons.The hypothesis: Employment (sheltered workshop, open or supported employment) of persons with ID, may enable these individuals to improve their oral health status, attitudes and behavior, compared to the ID individuals who are not working, due to the development of specific socio-emotional characteristics and dexterities.Evaluation of the hypothesis: According to previous reports, employed people with ID demonstrated better self-esteem and greater autonomy, more satisfaction with their vocational/non-vocational ac-tivities and higher quality of life.